Estimation of existing district heating distribution network from the standpoint of life cycle analysis - Rogoža, Artur (Journal of Civil Engineering and Management, 2003)
Life cycle analysis is a widespread method in most countries. Its principle is to evaluate direct and indirect influences of searching object on environment during its all life cycle. Life cycle model calculations of two existing district heating distribution networks were investigated in this case. Two variants of district heating network maintenance works were computed and compared: renovations using pipes assembled in channels and pre-insulated pipes technologies. Primary energy, heat losses, expenses for maintenance works and heat losses were calculated. The most suitable periodicities of maintenance works and character of the networks depreciation using those periodicities were determined.First Published Online: 26 Jul 2012